2022
DOI: 10.3389/fneur.2022.891415
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology of motor fatigue and fatigability in multiple sclerosis

Abstract: Multiple Sclerosis (MS) is a heterogeneous immune mediated disease of the central nervous system (CNS). Fatigue is one of the most common and disabling symptom of MS. It interferes with daily activities on the level of cognition and motor endurance. Motor fatigue can either result from lesions in cortical networks or motor pathways (“primary fatigue”) or it may be a consequence of detraining with subsequent adaptions of muscle and autonomic function. Programmed exercise interventions are used frequently to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 138 publications
(144 reference statements)
0
8
0
Order By: Relevance
“…Numbness includes paresthesia that are also associated with MS and TM and often accompany limb weakness. 31 These can be very distinct symptoms to patients and when MS is suspected, inquiring about tingling/burning/numbness/pins and needles sensations should occur if the patient does not volunteer this information. A particularly noteworthy and classic complaint is Lhermitte's sign, an "electric shock" sensation that travels down the patient's spine, propagating into the limbs.…”
Section: Vision (Visi)mentioning
confidence: 99%
“…Numbness includes paresthesia that are also associated with MS and TM and often accompany limb weakness. 31 These can be very distinct symptoms to patients and when MS is suspected, inquiring about tingling/burning/numbness/pins and needles sensations should occur if the patient does not volunteer this information. A particularly noteworthy and classic complaint is Lhermitte's sign, an "electric shock" sensation that travels down the patient's spine, propagating into the limbs.…”
Section: Vision (Visi)mentioning
confidence: 99%
“…Due to the ubiquitous presence of mitochondria, neuromuscular dysfunction may not solely result from ROS-associated damage within muscle fibers. Instead, ROS-mediated alterations at the level of the neuromuscular synapses, motor nerves and the central nervous system are known to contribute to weakness in a number of neuromuscular diseases [ 116 , 117 , 118 ].…”
Section: Structural and Functional Impairments Of Mitochondria In Icu...mentioning
confidence: 99%
“…Multiple sclerosis (MS) is characterized by focal as well as diffuse damage to the central nervous system (CNS), causing alterations in the autonomic nervous system (ANS) on the level of cardiac and vascular control [ 1 , 2 , 3 ]. During the course of the disease, about 50% of patients, including those with normal autonomic reflexes, report complaints of orthostatic intolerance (OI), accompanied by non-specific symptoms such as dizziness, fatigue, and vision changes [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations have shown that the risk of developing CAD increases with age, the progressive course of the disease, longer disease duration, greater disability, and fatigue symptoms [ 6 , 9 , 10 , 11 , 12 ]. Orthostatic dysregulation is not typically the initial manifestation of MS; however, it is associated with an increased risk of falls, cardiovascular events, cerebral hypoperfusion, and cognitive impairment [ 1 ].…”
Section: Introductionmentioning
confidence: 99%